The Dynamics of Tuberculosis through BSEIR Model with Immigration in Malaysia (Malaysian Journal of Fundamental and Applied Sciences, 2023)
Tuberculosis or known as TB is an airborne disease that exists in Malaysia caused by Mycobacterium Tuberculosis. Despite that, TB infection is curable with early diagnosis and treatment. The disease can be prevented through Bacillus Calmette-Guérin (BCG) vaccine, which is given among infants at birth. Numerous mathematical models on infectious diseases have been formulated in earlier studies since it is crucial to comprehend infectious disease transmission patterns and predict future outcomes. However, there is minimal study on the dynamics of TB transmission, particularly in Malaysia concerning immigration. Hence, this study aims to formulate a mathematical BCG-vaccinated, susceptible, exposed, infected, and recovered (BSEIR) model for TB infection in Malaysia by considering the immigration parameter. The model parameters are obtained from the literature and some with reported data in 2013 as initial value for the simulation using MAPLE software. The obtained results revealed that the basic reproduction number,  for the model is more than one. The graphical plot shows that the BSEIR model with immigration demonstrates a rise in TB-infected cases. The best strategy to lessen the number of infected individuals in Malaysia is by increasing the transmission rate and recovery rate. Additionally, the local stability analysis on the diseases-free equilibrium point and sensitivity analysis of its parameter is also provided and discussed. To conclude, a proper screening test should be mandated by the authorities before permitting new immigrants and refugees into Malaysia.
Keywords: Tuberculosis (TB) Model, Infectious Disease, Basic Reproduction, Disease-free equilibrium